1985
DOI: 10.1172/jci112243
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of granulation tissue formation by platelet-derived growth factor in normal and diabetic rats.

Abstract: Subcutaneous implantation of Hunt-Schilling wound chambers in rats induces a wound repair response causing the chamber first to fill with fluid and subsequently with connective tissue. The presence of a type I collagen gel encouraged a more rapid dispersion of cells throughout the chamber but had no effect on the rate of new collagen deposition. Addition of platelet-derived growth factor (PDGF; 50 ng/chamber) to the collagen-filled chambers caused an earlier influx of connective tissue cells, a marked increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
128
4
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(137 citation statements)
references
References 32 publications
4
128
4
1
Order By: Relevance
“…These data demonstrate that CTGF mRNA induction by TGF-f does not require de novo protein synthesis, indicating that the increase in CTGF mRNA is directly regulated by TGF-fl. tissue infiltration, neovascularization, and matrix deposition (Schilling et al, 1959;Hunt et al, 1967;and Grotendorst et al, 1985). (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These data demonstrate that CTGF mRNA induction by TGF-f does not require de novo protein synthesis, indicating that the increase in CTGF mRNA is directly regulated by TGF-fl. tissue infiltration, neovascularization, and matrix deposition (Schilling et al, 1959;Hunt et al, 1967;and Grotendorst et al, 1985). (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…The TGF-f1 transcript was present at the earliest times assayed with it highest level on day 3 followed by a rapid decrease to very low levels by day 9. Histological analysis of day 3 tissue reveals large numbers of leukocytes (Grotendorst et al, 1985) that produce TGF-fl (Assoian et al, 1987;. Interestingly, the CTGF transcript exhibits a very different pattern of expression with a peak on day 9 that coincides with the initial ingrowth of granulation tissue composed of connective tissue cells and vascular endothelial cells both of which express the CTGF mRNA in culture (Bradham et al, 1981).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common collection device has been the sponge [13,14,16], where cells invade and lay down collagen. Other studies have involved insertion of porous cylinders, most commonly the HuntSchilling stainless steel mesh cylinder [17]. These cylinders have been useful for the study of wound repair as they induce a response that exhibits the classic phases of inflammation, connective tissue infiltration, neovascularisation and matrix deposition [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Many reports have also demonstrated that exogenous PDGF can enhance angiogenesis. In mice, implantation of PDGF B-chain-transfected melanoma cells resulted in increased fibrovascular stroma development relative to untransfected cells.…”
mentioning
confidence: 99%